2022
DOI: 10.1093/eurheartj/ehac544.2804
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation virtual ward: reshaping the future of AF care

Abstract: Background Atrial fibrillation (AF) hospital admissions represent significant AF related treatment costs nationally. In the year 2019–2020 our hospital reported 1,333 admissions with a primary diagnosis of AF, with a 10% annual increase. A virtual ambulatory AF ward providing multidisciplinary care with remote hospital-level monitoring could reshape the future model of AF management. Methods An AF virtual ward was implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A consistent theme from received feedback was that the provision of remote monitoring enabled patients to feel safer in their own homes, better supported and more empowered to manage their health. We did encounter a small number of patients with an aversion or anxiety towards digital technologies, which is in keeping with feedback from similar AF virtual ward models [11,19].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A consistent theme from received feedback was that the provision of remote monitoring enabled patients to feel safer in their own homes, better supported and more empowered to manage their health. We did encounter a small number of patients with an aversion or anxiety towards digital technologies, which is in keeping with feedback from similar AF virtual ward models [11,19].…”
Section: Discussionmentioning
confidence: 81%
“…Most recently, UK colleagues in Leicester have developed a similar virtual ward model for AF using a digital remote monitoring platform [11]. These patients received more intensive monitoring, and were provided with single lead ECG recorders, pulse oximeters and Bluetooth-integrated blood pressure machines.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are particularly relevant to telehealth settings where ECG signals are recorded without clinical supervision. Several such settings arise in the detection and management of atrial fibrillation at home, including: (i) virtual wards to reduce hospitalisation for atrial fibrillation (42); (ii) screening for paroxysmal atrial fibrillation (43); and (iii) detecting recurrent atrial fibrillation after ablation or cardioversion (44). In each of these examples an accurate QRS detector is a key step in processing the intermittent ECGs acquired by patients at home, where signal quality may be lower than in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…This proof-of-concept study recently showed potential for decreasing AF hospital admissions and re-admissions. 111 …”
Section: Virtual Clinicsmentioning
confidence: 99%